An analysis of Indonesian literary translation ‘Pena Beracun’ by Suwarni A.S. from Agatha Christie’s novel The Moving Finger - Sigit Suharjono (UAD TEFL International Conference)
The work of translation is not a matter of only transferring words from one language to another. It is a communication bridge through which a translator must pick up and carry the message of the whole text that the writer is trying to communicate in the given situation of the source-text readers and deliver it to the target-text readers in their adopted and adapted situation. This is the point at which a translator often misses what is in the writer’s mind because s/he is unable to get into the writer’s mind to reveal the hidden message. As a result, the way the readers of the target text think and feel about what they read is often not the same as the way the readers of the source text do. This paper is aimed at finding out problems related to non-equivalence from the word level to the pragmatic level based on Baker’s that may be found in a literary translation of the first chapter of Pena Beracun by Suwarni A.S from Agatha Christie’s novel ‘The Moving Finger” and discusses the translator’s choices of the target text equivalence for the source text. The method of this study is a library research. The data was collected from two sources: Pena Beracun, an Indonesian translation of ‘The Moving Finger’ by Agatha Christie and its original English novel. The data collection technique was done by comparing the two sources to find non-equivalence problems from the word level to the textual level.  The problem(s) in the translator’s choice of TL equivalence for SL, which may range from choosing the equivalence at word level to the choice of textual equivalence was identified and discussed by referring to the strategies as proposed by Baker (2011).  Lots of cases of non-equivalence problems are found in the translation of the first chapter Pena Beracun by Suwarni A.S from Agatha Christie’s novel ‘The Moving Finger’ which range from non-equivalence at word level to textual level. Most of the problems of non-equivalence are related to collocation and fixed expressions. The translator’s strategies to overcome the problems are directed more to the acceptability and naturalness in the target language, giving style to the literary use of language.